FORMATTING MODAL OF AN INTEGRATED URBAN REGION DESIGNED FOR THE PRE-HOSPITALIZATION ASSISTANCE TRANSPORT SYSTEM - CORDEIRO, Dirac; CORDEIRO, Gauss Moutinho; LIMA NETO, Oswaldo (Brazilian Journal of Biometrics, 2016)
The mobile pre-hospitalization service for individuals is a specialized assistance service outside the hospital establishments. The intention of this type of service is to maximize the assistance aiming to preserve life. The purpose of this kind of service is to provide to the user – the person who suffered an accident in a certain region R, the shortest response time after the incident occurred. The means of transport for the removal of the victims to the hospital establishments is done by a service unit (Us). In this way, the substantial increase in the value curve expected for the assistance throughout time is a very well known fact. For the pre-hospitalization service, a city can be treated as a single urban region of assistance or can be stratified into urban zones of service. For the first case, a single station or location serves as the screening headquarters – the locality is used as a distributor of the Us and, in this case, the patient is removed to the closest hospital establishment, where the user of the system (accident victim) is located. The second case, in each assistance zone (ZA) is hospital establishment is allocated, such as, public and private establishments of the municipality or the state in accordance with the National Health System (NHS). In this way, the model to be approached for assistance in a region is the representation of the urban areas of the city and the urban zones of assistance (ZA) as a function of the area elements of the region that contain a hospital organization. In short, each one of the zones of assistance is defined to minimize the time response (TR) between the call to the Us and the arrival of the service to the victim.